Radiosensitivity in individuals with tuberous sclerosis complex - Kuhlmann, Lukas; Stritzelberger, Jenny; Fietkau, Rainer; Distel, Luitpold; Hamer, Hajo (Discover Oncology, 2024)
Benign tumors, but rarely cancer, are common in patients with tuberous sclerosis complex (TSC). Blood samples from patients undergoing treatment for TSC at our institution were analyzed for their individual sensitivity to ionizing radiation. Blood samples were collected from 13 adult patients with TSC. The samples were irradiated ex vivo and analyzed by 3-color fluorescence in situ hybridization. In each patient, aberrations were analyzed in 200 metaphases of chromosomes 1, 2, and 4 and scored as breaks. Radiosensitivity was determined by mean breaks per metaphase (B/M) and compared to both healthy donors and oncologic patients. The radiosensitivity (B/M) of the TSC patient cohort (n = 13; female: 46.2%, B/M: 0.48 ± 0.11) was clearly increased compared to healthy individuals of similar age (n = 90; female: 54.4%; B/M: 0.40 ± 0.09; p = 0.001). There was no difference compared to age-matched oncological patients (n = 78; female: 67.9%; B/M 0.49 ± 0.14; p = 0.246). Similarly, the proportion of radiosensitive (B/M > 0.5) and distinctly radiosensitive individuals (B/M > 0.6) was increased in the TSC and oncological patient cohorts (TSC: 30.8% and 7.7%, oncological patients: 46.2% and 14.1%) compared to the healthy individuals (11.1% and 2.2%). Although patients with TSC develop mostly benign and rarely malignant tumors, they are similarly sensitive to radiation as patients with malignant tumors.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Chromosomal aberrations; In situ hybridization; Ionizing radiation; Radiosensitivity; TSC1; TSC2; Tuberous sclerosis complex